Characterization and catalytic activity of cobalt containing MCM-41 prepared by direct hydrothermal, grafting and immobilization methods - Bhoware, Shrikant S.; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
{Cobalt containing hexagonal mesoporous molecular sieves (MCM-41) were prepared by different methods viz., direct hydrothermal synthesis, grafting and immobilization. The calcined material was characterized by various spectroscopic tools such as powder X-ray diffraction (XRD), N-2 adsorption-desorption isotherms, Fourier transformed infra-red (Fr-IR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), diffuse reflectance UV-vis and X-ray photoelectron spectroscopy (XPS). The XRD patterns show the highly intense (100) reflection peak in the range 2-3 degrees (2 theta angle), characteristic of mesoporous material. Higher order reflection peaks suggest highly ordered mesoporous structure. N2 adsorption-desorption isotherms are of type IV according to IUPAC classification and the steep rise in the isotherms in the narrow range 3.5-4.5 of relative pressure (P/P-0) is due to the condensation of N-2 gas molecules in the pores (characteristic of mesoporous structure). In FT-IR increase in the intensity of band at 960 cm(-1) with the increase of the cobalt content in Co-MCM-41 samples indicate the incorporation of cobalt ions in the framework of MCM-41. SEM and TEM reveal spherical morphology for the cobalt substituted MCM-41. UV-vis spectra demonstrate the characteristic features of framework and extraframework cobalt in MCM-41. Cobalt is in +2 oxidation state as evidenced from UV-vis and XPS. The catalysts were tested for the side chain oxidation of ethylbenzene using 70 wt.% tert-butyl hydrogen peroxide as an oxidant with and without the use of solvent. Solvents have effect in the catalytic activity and selectivity. In the absence of solvent, substituted cobalt [
Keywords: 2-butanol; cyclohexanone; Mesoporous molecular sieves; MPV reduction